Kontekstualisasi Pemahaman dan Hukuman Gratifikasi dalam Perspektif Hadis - Khasanah, Sofiatun (Jurnal Riset Agama, 2022)
This research aims to discuss contextualization of the understanding of Gratification in Hadith. This research applies a type of qualitative research conducted with library studies and uses tahlili methods and contextualization. The results and discussions of this study include an overview of corruption and gratification, actions that include gratification, punishment in the world and the afterlife of gratification actors contained in the Qur'an, Hadith, and applicable laws. This study concluded that the act of gratification has existed since the time of the Prophet, where there are many differences in terms of social conditions, culture, and a more modern era. Then there needs to be contextualization of hadith in the legal system and the definition of corruption. This study outlines how contextualizing the understanding and punishment of gratification in hadith as the times progress.